Spatial And Temporal Changes in physico-chemical and Biological Parameters of Panangad Region of Vembanad Lake - Jyotsna Rajeswari, K. (Dept.of Fishery Hydrography, 2016)
Abstract- The present investigation has been carried out for determining the various physico-chemical and biological parameters prevailing in Vembanad Lake of Panangad region Cochin. The water samples were collected fortnightly from the three stations namely, Panangad-Kumbalam (S1), Nettoor (S2) and Kundannoor (S3) for a period of ten months (September, 2015 to June, 2016). The analysis showed that the mean maximum temperature was 29.320C in Panangad-Kumbalam region while minimum of 28.00C in Nettoor. The mean maximum of pH, among the three locations was recorded in Nettoor region (7.8) and the mean minimum was recorded in Kundannoor (7.7). DO had highest mean of 5.2mg/l in Panangad-Kumbalam while the lowest of 3.8mg/l in Kundannoor. The mean maximum alkalinity was recorded in Nettoor (118.7mg/l) and the mean minimum was recorded in Kundannoor (101.7mg/l). The mean of transparency was recorded in Panangad-Kumbalam (62.8cm) while mean minimum transparency was recorded in Nettoor (36.6cm). When compared to the three stations Panangad- Kumbalam had the mean maximum of Nitrite (1.5mmol/l) and mean minimum of Nitrite was in Kundannoor (0.73mmol/l). The mean maximum of Nitrate (10.7mmol/l) was recorded in Panangad-Kumbalam and the mean minimum of Nitrate (7.5mmol/l) was recorded in Nettoor. In case of phosphate, the mean maximum (3.63mmol/l) was recorded in Nettoor and mean minimum (3.2mmol/l) was recorded in Panangad-Kumbalam. Diatoms are most dominant species in three regions. Among zooplankton copepods are dominantly seen in the study regions. Among aquatic weeds, Eichornia crassipes was dominantly seen in all the regions in all the seasons. Five species of shell fishes are collected during the study period which belongs to the order Decapoda. 24 species of fin fishes are collected during the study period. The fishes can be categorized into eight orders and 18 families. The study indicates the necessity of a detailed investigation on the co-relation between abiotic and biotic factors.